PENGARUH QUICK RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sarnawia Rehalat; Jaelani Lamasidonda; Syawal Zakaria (Indo-Fintech Intellectuals: Journal of Economics and Business, 2022)
The purpose of this study is to determine and analyze the effect of quick ratio and earnings per share on share prices in coal mining companies listed on the Indonesia Stock Exchange (IDX). The analytical tool used in this study was multiple linear regression. The total population of 21 companies or all coal mining companies listed on the IDX, which is sampled in this study is as many as 6 stone mining companies listed on the IDX and companies have data to calculate Quick Ratio (QR) and Earning Per Share (EPS), as well as available annual financial report data published during the research period 2011-2016 in www.idx.co.id. The results showed that the independent variable Quick Ratio (X1) had a negative and significant influence on stock prices, while Earning Per Share (X2) had a positive but not significant influence on Coal Mining Companies listed on the IDX. The higher the Quick Ratio level indicates its short-term financial performance, the better because the company is considered capable of paying its obligations using cash, tradable securities, and receivables